2021
DOI: 10.3390/pharmaceutics13050699
|View full text |Cite
|
Sign up to set email alerts
|

Competition (‘Steal’ Phenomenon) between [68Ga]Ga-PSMA-11 Uptake in Prostate Tumor Tissue Versus Healthy Tissue

Abstract: We aimed to clarify whether a steal ‘phenomenon’ exists by investigating if uptake of ‘prostate specific membrane antigen’ (PSMA) in prostate tumor tissue correlates with the uptake in healthy tissue. Patients with prostate cancer referred for a [68Ga]Ga-PSMA-11 PET/CT were identified retrospectively. Semi-automated quantitative image analysis was performed; fractional healthy tissue [68Ga]Ga-PSMA-11 uptake volume (HT-PSMA (SUV*cm3)) in the lacrimal, submandibular, and parotid glands, and kidneys, and the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the current study, however, the number of treatment cycles has a direct relationship with the occurrence of significant bone marrow toxicity, which suggests that while dose-de-escalation may be effective in mitigating the impact of treatment on salivary gland function, administering more cycles of treatment exposes the patients to a higher risk of significant hematologic toxicity. Some recent studies have shown the dynamics of radioligand uptake in normal organs as a function of tumor burden [37,38,39]. These studies, mostly validating the concept of the "tumor sink effect," support our dose-de-escalation practice.…”
Section: Discussionmentioning
confidence: 65%
“…In the current study, however, the number of treatment cycles has a direct relationship with the occurrence of significant bone marrow toxicity, which suggests that while dose-de-escalation may be effective in mitigating the impact of treatment on salivary gland function, administering more cycles of treatment exposes the patients to a higher risk of significant hematologic toxicity. Some recent studies have shown the dynamics of radioligand uptake in normal organs as a function of tumor burden [37,38,39]. These studies, mostly validating the concept of the "tumor sink effect," support our dose-de-escalation practice.…”
Section: Discussionmentioning
confidence: 65%
“…Fourth, PERCIST for the lesion-based response evaluation is not validated for PSMA PET/CT. However, it is already broadly available in clinical practice and easy to apply [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PET reconstruction was obtained following the EANM Research Ltd. (EARL), Vienna, Austria recommendations although its use for [ 68 Ga]Ga-PSMA-11 PET/CT interpretation has not been validated yet [ 14 , 15 ]. The [ 68 Ga]Ga-PSMA-11 accumulation was corrected for lean body mass (in SUV lbm,peak *cm 3 ) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%